Life cycle assessment of concrete intervention strategies for the repair and prevention of a corrosion-damaged canopy - Renne Neel; Moins Ben; Buyle Matthias; Audenaert Amaryllis; Craeye Bart (MATEC Web of Conferences)
Considering the emerging need for more sustainable practices, life-extending interventions in the concrete sector are gaining interest. This paper focuses on a life cycle assessment of repair and prevention strategies for corrosion-related damage using a case study. Eleven intervention strategies based on the EN 1504-9 principles, categorized under four methods, are considered to extend the service life of the canopy of a recreational facility in Belgium for 25 and 50 years: (i) PR: patch repair (with surface protection) i.e. local removal of delaminated concrete, (ii) CR: conventional repair (with surface protection) i.e. extensive removal of contaminated concrete, (iii) GCP: galvanic cathodic protection, and (iv) ICCP: impressed current cathodic protection. Overall, the combination of CR at the beams and slabs with PR at the columns can be considered the most optimal intervention strategy based on the single score and three out of six key midpoints: carcinogenic human toxicity, non-carcinogenic human toxicity and fine particulate matter formation. Alternatively, the ICCP scenarios, particularly those with discrete anodes and titanium strips, also perform well, especially in terms of global warming potential, freshwater ecotoxicity, and marine ecotoxicity. Finally, for a 25-year service life extension scenario, the combination of CR and PR achieves the lowest impacts across all dominant midpoint indicators and single score.